Influences of the area, shape and connectivity of coastal lakes on the taxonomic and functional diversity of fish communities in Southern Brazil - Hartz, Sandra Maria; Rocha, Elise Amador; Brum, Fernanda Thiesen; Luza, André Luís; Guimarães, Taís de Fátima Ramos; Becker, Fernando Gertum (Zoologia (Curitiba, Brazil), 2019)
In this study we investigated the influence of landscape variables on the alpha taxonomic and functional diversity of fish communities in coastal lakes. We built an analytical framework that included possible causal connections among variables, which we analyzed using path analysis. We obtained landscape metrics for the area, shape and connectivity (estuary connectivity and primary connectivity to neighboring lakes) of 37 coastal lakes in the Tramandaí River Basin. We collected fish data from 49 species using standardized sampling with gillnets and obtained a set of traits related to dispersal abilities and food acquisition. The model that best explained the taxonomic diversity and functional richness took into account the shape of the lakes. Functional richness was also explained by estuary connectivity. Functional evenness and dispersion were not predicted by area or connectivity, but they were influenced by the abundant freshwater species. This indicates that all lakes support most of the regional functional diversity. The results highlight the importance of the dispersal process in this lake system and allow the conclusion that considering multiple diversity dimensions can aid the conservation of local and regional fish communities.